giải các phương trình sau :
a) \(\dfrac{x-1}{x+1}-\dfrac{1}{x}=\dfrac{2}{x\left(x+1\right)}\)
Giải các phương trình sau:
1. \(a,\dfrac{6}{x-1}-\dfrac{4}{x-3}=\dfrac{8}{2x-6}\)
\(b,\dfrac{1}{x-2}+\dfrac{5}{x+1}=\dfrac{3}{2-x}\)
\(c,\dfrac{3x}{x-2}-\dfrac{x}{x-5}=\dfrac{3x}{\left(x-2\right)\left(5-x\right)}\)
2. \(a,\left(x+2\right)\left(3-4x\right)=x^2+4x+4\)
\(b,2x^2-6x+1\)
1a.
ĐKXĐ: \(x\ne\left\{1;3\right\}\)
\(\Leftrightarrow\dfrac{6}{x-1}=\dfrac{4}{x-3}+\dfrac{4}{x-3}\)
\(\Leftrightarrow\dfrac{3}{x-1}=\dfrac{4}{x-3}\Leftrightarrow3\left(x-3\right)=4\left(x-1\right)\)
\(\Leftrightarrow3x-9=4x-4\Rightarrow x=-5\)
b.
ĐKXĐ: \(x\ne\left\{-1;2\right\}\)
\(\Leftrightarrow\dfrac{5}{x+1}=\dfrac{3}{2-x}+\dfrac{1}{2-x}\)
\(\Leftrightarrow\dfrac{5}{x+1}=\dfrac{4}{2-x}\Leftrightarrow5\left(2-x\right)=4\left(x+1\right)\)
\(\Leftrightarrow10-2x=4x+4\Leftrightarrow6x=6\Rightarrow x=1\)
1c.
ĐKXĐ: \(x\ne\left\{2;5\right\}\)
\(\Leftrightarrow\dfrac{3x\left(x-5\right)}{\left(x-2\right)\left(x-5\right)}-\dfrac{x\left(x-2\right)}{\left(x-2\right)\left(x-5\right)}=\dfrac{-3x}{\left(x-2\right)\left(x-5\right)}\)
\(\Leftrightarrow3x\left(x-5\right)-x\left(x-2\right)=-3x\)
\(\Leftrightarrow2x^2-10x=0\Leftrightarrow2x\left(x-5\right)=0\Rightarrow\left[{}\begin{matrix}x=0\\x=5\left(loại\right)\end{matrix}\right.\)
2a.
\(\Leftrightarrow-4x^2-5x+6=x^2+4x+4\)
\(\Leftrightarrow5x^2+9x-2=0\Rightarrow\left[{}\begin{matrix}x=-2\\x=\dfrac{1}{5}\end{matrix}\right.\)
2b.
\(2x^2-6x+1=0\Rightarrow x=\dfrac{3\pm\sqrt{7}}{2}\)
giải các phương trình sau
1, \(\dfrac{2x}{x-1}-\dfrac{3}{x+3}=\dfrac{x^2+3}{\left(x+1\right)\left(x-3\right)}\)
2,\(\dfrac{x}{x-3}-\dfrac{1}{x+2}=\dfrac{4x+3}{\left(x-3\right)\left(x+2\right)}\)
giải các phương trình sau
\(\dfrac{2}{x+1}\)-\(\dfrac{1}{x-2}\)=\(\dfrac{3x-11}{\left(x+1\right)\left(x-2\right)}\)
\(x\ne-1,x\ne2\\ \Leftrightarrow2x-4-x-1=3x-11\\ 6=2x\\ x=6:2=3_{\left(tmđk\right)}\)
giải các phương trình sau
a, 4x- 2(1-x)= 5(x-4)
b, \(\dfrac{x}{6}+\dfrac{1-3x}{9}=\dfrac{-x+1}{12}\)
c, \(\left(x+2\right)^2-3\left(x+2\right)=0\)
d,\(\dfrac{x-5}{x}+\dfrac{x-3}{x+5}=\dfrac{x-25}{x\left(x+5\right)}\)
a: Ta có: \(4x-2\left(1-x\right)=5\left(x-4\right)\)
\(\Leftrightarrow4x-2+2x=5x-20\)
\(\Leftrightarrow x=-18\)
b: Ta có: \(\dfrac{x}{6}+\dfrac{1-3x}{9}=\dfrac{-x+1}{12}\)
\(\Leftrightarrow6x+4\left(1-3x\right)=3\left(-x+1\right)\)
\(\Leftrightarrow6x+4-12x=-3x+3\)
\(\Leftrightarrow-3x=-1\)
hay \(x=\dfrac{1}{3}\)
c: Ta có: \(\left(x+2\right)^2-3\left(x+2\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=1\end{matrix}\right.\)
d: Ta có: \(\dfrac{x-5}{x}+\dfrac{x-3}{x+5}=\dfrac{x-25}{x\left(x+5\right)}\)
\(\Leftrightarrow x^2-25+x^2-3x=x-25\)
\(\Leftrightarrow2x^2-4x=0\)
\(\Leftrightarrow2x\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\left(loại\right)\\x=2\left(nhận\right)\end{matrix}\right.\)
giải các phương trình sau
a, 3x -(3x+2) =x+3
b, \(\dfrac{5x-1}{4}+\dfrac{2x-1}{3}=\dfrac{3x}{2}\)
c, \(\left(x^2-3^2\right)+2\left(x-3\right)=0\)
d,\(\dfrac{1}{x-1}+\dfrac{2}{1+x}-\dfrac{4x+6}{x^2-1}=0\)
a: Ta có: \(3x-\left(3x+2\right)=x+3\)
\(\Leftrightarrow x+3=-2\)
hay x=-5
b: Ta có: \(\dfrac{5x-1}{4}+\dfrac{2x-1}{3}=\dfrac{3x}{2}\)
\(\Leftrightarrow15x-3+8x-4=18x\)
\(\Leftrightarrow5x=7\)
hay \(x=\dfrac{7}{5}\)
giải phương trình sau \(\dfrac{\dfrac{x+1}{x-1}-\dfrac{x-1}{2\left(x+1\right)}}{1+\dfrac{x+1}{x-1}}=\dfrac{x-1}{2\left(x+1\right)}\)
\(ĐK:x\ne-1;x\ne1\\ PT\Leftrightarrow\dfrac{\dfrac{2x^2+4x+2-x^2+2x-1}{2\left(x+1\right)\left(x-1\right)}}{\dfrac{x-1+x+1}{x-1}}=\dfrac{x-1}{2\left(x+1\right)}\\ \Leftrightarrow\dfrac{x^2+6x+1}{2\left(x-1\right)\left(x+1\right)}\cdot\dfrac{x-1}{2x}=\dfrac{x-1}{2\left(x+1\right)}\\ \Leftrightarrow\dfrac{x^2+6x+1}{4x\left(x+1\right)}=\dfrac{x-1}{2\left(x+1\right)}\\ \Leftrightarrow x^2+6x+1=2x\left(x-1\right)\\ \Leftrightarrow x^2+6x+1=2x^2-2x\\ \Leftrightarrow x^2-8x-1=0\\ \Leftrightarrow\left[{}\begin{matrix}x=4+\sqrt{17}\left(tm\right)\\x=4-\sqrt{17}\left(tm\right)\end{matrix}\right.\)
Giải các phương trình sau:
\(j.\dfrac{1}{x-1}-\dfrac{7}{x-2}=\dfrac{1}{\left(x-1\right)\left(2-x\right)}\)
\(k.\dfrac{2x+19}{5x^2-5}-\dfrac{17}{x^2-1}=\dfrac{3}{1-x}\)
\(l.\dfrac{1}{x-1}-\dfrac{2x^2+5}{x^3-1}=\dfrac{4}{x^2+x+1}\)
Giải phương trình sau:
\(\left(\dfrac{1}{x}+2\right)\left(2+\dfrac{x+1}{x-1}\right)=\left(\dfrac{1}{x}+2\right)\left(x+2\right)\)
\(ĐK:x\ne0;x\ne1\\ PT\Leftrightarrow\left(\dfrac{1}{x}+2\right)\left(2+\dfrac{x+1}{x-1}-x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}\dfrac{1}{x}=-2\\\dfrac{x+1}{x-1}=x\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x+1=x^2-x\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x^2-2x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x=1+\sqrt{2}\\x=1-\sqrt{2}\end{matrix}\right.\)
a\(8\left(x+\dfrac{1}{x}\right)^{2^{ }}+4\left(x^{2^{ }}+\dfrac{1}{x^2}\right)-4\left(x^2+\dfrac{1}{x^2}\right)\left(x+\dfrac{1}{x}\right)=\left(x+4\right)^2\)giải các phương trình\(\dfrac{x+4}{2x^2-5x+2}+\dfrac{x+1}{2x^2-7x+3}=\dfrac{2x+5}{2x^2-7x+3}\)
b)
ĐKXĐ: \(x\notin\left\{2;3;\dfrac{1}{2}\right\}\)
Ta có: \(\dfrac{x+4}{2x^2-5x+2}+\dfrac{x+1}{2x^2-7x+3}=\dfrac{2x+5}{2x^2-7x+3}\)
\(\Leftrightarrow\dfrac{x+4}{\left(x-2\right)\left(2x-1\right)}+\dfrac{x+1}{\left(x-3\right)\left(2x-1\right)}=\dfrac{2x+5}{\left(2x-1\right)\left(x-3\right)}\)
\(\Leftrightarrow\dfrac{\left(x+4\right)\left(x-3\right)}{\left(x-2\right)\left(2x-1\right)\left(x-3\right)}+\dfrac{\left(x+1\right)\left(x-2\right)}{\left(x-2\right)\left(x-3\right)\left(2x-1\right)}=\dfrac{\left(2x+5\right)\left(x-2\right)}{\left(2x-1\right)\left(x-3\right)\left(x-2\right)}\)
Suy ra: \(x^2-3x+4x-12+x^2-2x+x-2=2x^2-4x+5x-10\)
\(\Leftrightarrow2x^2-14=2x^2+x-10\)
\(\Leftrightarrow2x^2-14-2x^2-x+10=0\)
\(\Leftrightarrow-x-4=0\)
\(\Leftrightarrow-x=4\)
hay x=-4(nhận)
Vậy: S={-4}